0474 Long-Term Efficacy and Safety of Lemborexant in Elderly Adults with Insomnia Disorder: Results from SUNRISE-2. (27th May 2020) - Moline, M; Inoue, Y; Pinner, K; Perdomo, C; Filippov, G; Kubota, N; Yardley, J
Abstract: Introduction: In SUNRISE-2 (NCT02952820; E2006-G000-303), the dual orexin receptor antagonist lemborexant (LEM) demonstrated significant benefit versus placebo (PBO) on subjective sleep endpoints over 6mo in subjects age ≥18y; benefits were sustained over 12mo. Here we present 12mo efficacy and safety data for LEM from the elderly (≥65y) subgroup. Methods: SUNRISE-2 was a 12mo, randomized, double-blind, PBO-controlled (first 6mo [Period 1]), global phase 3 study. During Period 1, subjects were randomized to PBO or LEM (5mg, [LEM5]; 10mg, [LEM10]). During Period 2 (second 6mo), LEM subjects continued their assigned dose while PBO subjects were rerandomized to LEM5 or LEM10 (not reported here). Patient-reported (subjective) sleep endpoints were assessed from sleep diary data (sleep onset latency [sSOL]; sleep efficiency [sSE]; wake after sleep onset [sWASO]). Results: Of the 949 subjects in the Full Analysis Set, 262 were age ≥65y. At 6mo, in subjects ≥65y, median sSOL significantly decreased from baseline for LEM5 (−21.7) and LEM10 (−26.0) versus PBO (−10.8; P <0.0001, P <0.01, respectively). At 12mo, LEM5 and LEM10 subjects maintained decreases in median sSOL (−29.3, −34.3, respectively). At 6mo, the mean (SD) increase from baseline in sSE was significantly larger versus PBO (8.5[13.3]) for LEM5 (16.9[13.6]; P <0.001) and LEM10 (14.9[15.9]; P <0.01). At 12mo, mean (SD) increase in sSE was maintained for LEM5 (18.1[12.5]) and LEM10 (18.0[16.8]). At 6mo, mean (SD) change from baseline in sWASO was significantly decreased versus PBO (−26.5 [52.9]) for LEM5 and LEM10 (−54.8[64.4], P <0.01; −51.4[69.3], P <0.05, respectively). At 12mo, mean (SD) decrease in sWASO was maintained for LEM5 (−58.6[46.0]) and LEM10 (−60.9[80.4]). Over 12mo, the most common (>10% either group) treatment emergent adverse events with LEM5 and LEM10, respectively, were somnolence (9.3%, 19.0%), nasopharyngitis (9.3%, 10.7%), and headache (10.5%, 6.0%). Conclusion: In elderly subjects, LEM demonstrated efficacy at 6mo, which persisted at 12mo; LEM was well tolerated. Support: Eisai Inc.